Fever of Unknown Origin - A Child With an Unusual Case of Juvenile Idiopathic Arthritis - Gyawali, Purnima; Gyawali, Deepika; Acharya, Sharda (Nepalese Medical Journal, 2020)
Fever of unknown origin in the pediatric population is fever >38.3°C (101°F) of at least seven days' duration, in which no diagnosis is apparent after initial outpatient or hospital evaluation that includes a careful history and physical examination and initial laboratory assessment. Fever of unknown origin is a diagnostic challenge, with a broad spectrum of causes classified as infectious, malignant/neoplastic, rheumatic/inflammatory, and miscellaneous disorders. A high index of suspicion should be kept for juvenile idiopathic arthritis in children presenting with unexplained fever and joint symptoms and should be appropriately managed. The case described here is of a 13-year-old female from Nepal, who presented to the Pediatric outpatient department of KIST Medical College and Teaching Hospital with a history of fever and arthralgia for three months.